Ultrasound-assisted green synthesis of silver nanoparticles using Ruta graveolens L. Extract and antitumor evaluation - Nikita Gandlevskiy; Altevir Rossato Viana; Gabriel Toneto Druzian; Daiana Kaminski Oliveira; Andre Passaglia Schuch; Alessandro Barge; Giancarlo Cravotto; Erico Marlon Moraes Flores (Ultrasonics Sonochemistry)
This study aims to evaluate the ultrasound-assisted synthesis of silver nanoparticles (AgNPs) based on an aqueous extract of Ruta graveolens L. to reduce Ag+ to Ag0. In addition, the biological activity of the synthesized AgNPs was evaluated against tumor cells. The following parameters were evaluated for the synthesis: proportion between Ag+ solution (0.1 mol L-1 Ag+) and R. graveolens L. extract, pH of R. graveolens L. extract (5, 7, and 9), temperature of solution containing Ag+ and R. graveolens L. extract, ultrasound (US) type (bath and probes), and the parameters for US as frequency (37, and 80 kHz for bath and 20 kHz for probes), amplitude and time of application of US. In order to confirm the US effect, “silent” experiments (without US) were performed. Using the optimized conditions (US bath, proportion between Ag+ solution and R. graveolens L. of 1 + 5, v v-1, 80 kHz, 70 % amplitude, 70 °C, pH 9, and 25 min of sonication time) it was possible to obtain mean size, PI, and zeta potential of AgNPs of 30 nm, 0.129, −34.44 mV, respectively. For comparison of results, AgNPs synthesized in the “silent” condition presented mean size, PI, and zeta potential of 66 nm, 0.412, and –22.12 mV, respectively. The US synthesized AgNPs were lower, more uniform, and stable when compared with magnetic stirring. In addition, the morphology of AgNPs using US was predominantly spherical and monodisperse. The biological activity using cell lines HaCat (keratinocytes), L929 (fibroblasts), and B16-F10 (melanoma) against nanoparticles synthesized using US was evaluated against the different cell lines and the antioxidant activity of the AgNPs was measured by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. A higher cytotoxic effect on the melanoma cell line (IC50 = 2.12 µg mL−1) compared to normal cells. A good result was found in the DPPH assay, with an IC50 of 234.3 µg mL−1 for free radical scavenging. Therefore, the US technology presents a promising and sustainable green method avoiding the use of toxic reagents and obtained AgNPs showed potent anticancer activity.